2022
DOI: 10.1158/1078-0432.ccr-21-2049
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of AMPK Leads to Attenuation of Antigen Presentation and Immune Evasion in Lung Adenocarcinoma

Abstract: Statement of Translational relevance: LKB1 inactivation in NSCLC is clinically relevant as it leads to resistance to immune checkpoint inhibitors. The findings of this study provide evidence that this immune evasion is due to subsequent inactivation of AMPK and attenuation of antigen presentation and suggest that restoration of AMPK activity could increase the number of patients benefiting from immunotherapy. Furthermore, the study expands the correlation between immune evasion and LKB1 mutations to include a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…AMPK can also epigenetically modulate gene transcription by phosphorylating demethylase TET2 and/or methyltransferase EZH2 33,34 . Moreover, a recent study has found that AMPK can reduce immune evasion by promoting antigen presentation 35 . On the other hand, AMPK is essential for KRAS‐driven tumorigenesis and cancer cell survival 36 ; in addition, it is crucial for the resistance of energy stress–induced oxidative damage 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK can also epigenetically modulate gene transcription by phosphorylating demethylase TET2 and/or methyltransferase EZH2 33,34 . Moreover, a recent study has found that AMPK can reduce immune evasion by promoting antigen presentation 35 . On the other hand, AMPK is essential for KRAS‐driven tumorigenesis and cancer cell survival 36 ; in addition, it is crucial for the resistance of energy stress–induced oxidative damage 37 .…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 Moreover, a recent study has found that AMPK can reduce immune evasion by promoting antigen presentation. 35 On the other hand, AMPK is essential for KRAS‐driven tumorigenesis and cancer cell survival 36 ; in addition, it is crucial for the resistance of energy stress–induced oxidative damage. 37 The regulation of autophagy by AMPK can also promote the survival of tumor cells in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…AMPKα-1-mediated inhibition of mTORC1 activity in cytotoxic T lymphocytes (CTLs) is required for CD8 + T-cell memory ( 140 ). Previous studies have revealed that inactivation of both AMPK α 1 and α 2 coupled with Kirsten rat sarcoma virus (KRAS) activation promotes tumorigenesis and decreases the infiltration of CD8 + /CD4 + T cells ( 141 ). Braverman et al., have reported that increasing AMPK activity orchestrates oxidative metabolism, proliferation, and in vitro recovery of human CD4 + T cells.…”
Section: Molecular Crosstalk Of Ampk Drives Anti-tumor Immune Respons...mentioning
confidence: 99%
“…Tumor-associated macrophages (TAMs) are present in abundance across various types of malignant tumors and promote tumor angiogenesis, extravasation and metastasis ( 144 ).Macrophages are responsible for driving anti-tumor immunity via phagocytosis and antigen presentation. Macrophages exist in two distinct phenotypes namely, the ‘classically’ activated, tumoricidal phenotype, M1φ, and the ‘alternatively’ activated pro-tumorigenic phenotype, M2φ ( 145 ).Some documented results indicate that AMPK inhibition leads to an up-surge in LPS-induced macrophage inflammatory function ( 141 ). Previous reports also state that AMPK prevents the polarization of monocyte-derived macrophages towards the M2φ subtype ( 146 ).Chiang et al., reported that metformin-mediated AMPK activation suppresses the skewing of macrophage towards M2φ subtype in breast cancer cells ( 147 ).…”
Section: Molecular Crosstalk Of Ampk Drives Anti-tumor Immune Respons...mentioning
confidence: 99%
“…A prospective study about cytokine profiles in NSCLC patients receiving ICI treatment in the second line revealed that patients with elevated expression of IFN-γ significantly benefit from PD-1 blockers ( 61 ). Moreover, attenuated antigen presentation was also found in NSCLC with compromised LKB1 and AMPK activity ( 62 ). Low expression of KAT2B concurrent with a higher frequency of somatic genes mutation was associated with lower response efficacy to ICIs in NSCLC patients, while KAT2B was linked to IFN-γ regulation, antigen processing, and presentation ( 63 ).…”
Section: Mechanisms Of Immunotherapy Resistance In Nsclcmentioning
confidence: 99%